Antimicrobial and Wound Healing Properties of FeO Fabricated Chitosan/PVA Nanocomposite Sponge - Anbazhagan Sathiyaseelan; Kandasamy Saravanakumar; Arokia Vijay Anand Mariadoss; Myeong-Hyeon Wang (MDPI AG, 2021)
Diabetic and anemia-associated diabetic wounds increase the considerable morbidity and mortality in people, as reported by clinical studies. However, no anemia-associated diabetic wound dressing materials have been developed until now. Hence, this study aimed to develop a nanocomposite scaffold composed of chitosan (CS), poly (vinyl alcohol) (PVA), and phytogenic iron oxide nanoparticles (FeO NPs), for accelerated anemia-associated diabetic wound healing. The aqueous leaves extract of Pinus densiflora (PD) was utilized for the synthesis of iron oxide nanoparticles (FeO NPs). TEM and elemental analysis confirmed smaller size PD-FeO NPs (<50 nm) synthesis with the combination of iron and oxide. In addition, in vitro biological studies displayed the moderate antioxidant, antidiabetic activities, and considerable antibacterial activity of PD-FeO NPs. Further, the different concentrations of PD-FeO NPs (0.01, 0.03, and 0.05%) incorporated CS/PVA nanocomposites sponges were developed by the freeze-drying method. The porous structured morphology and the presence of PD-FeO NPs were observed under FE-SEM. Among nanocomposite sponges, PD-FeO NPs (0.01%) incorporated CS/PVA sponges were further chosen for the in vitro wound-healing assay, based on the porous and water sorption nature. Furthermore, the in vitro wound-healing assay revealed that PD-FeO NPs (0.01%) incorporated CS/PVA has significantly increased the cell proliferation in HEK293 cells. In conclusion, the CS/PVA-PD-FeO NPs (0.01%) sponge would be recommended for diabetic wound dressing after a detailed in vivo evaluation.